2020
DOI: 10.1101/2020.04.29.20082867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ACE2 and TMPRSS2 expression by clinical, HLA, immune, and microbial correlates across 34 human cancers and matched normal tissues: implications for SARS-COV-2 COVID-19

Abstract: Background: Pandemic COVID-19 by SARS-COV-2 infection is facilitated by the ACE2 receptor and protease TMPRSS2. Modestly sized case series have described clinical factors associated with COVID-19, while ACE2 and TMPRSS2 expression analyses have been described in some cell types. Cancer patients may have worse outcomes to COVID-19. Methods:We performed an integrated study of ACE2 and TMPRSS2 gene expression across and within organ systems, by normal versus tumor, across several existing databases (The Cancer Ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 48 publications
(61 reference statements)
0
22
0
Order By: Relevance
“…Another point to consider is the effect of tumor microenvironment on ACE2 protein expression in some head and neck locations where the epithelia analyzed may be derived from tumor samples. It has recently been reported that in some cancers from different tissue types, the gene expression of ACE2 was significantly higher in normal tissues compared to matched tumors [ 49 ]. Further studies will be required to identify potential factors that may contribute to this change.…”
Section: Discussionmentioning
confidence: 99%
“…Another point to consider is the effect of tumor microenvironment on ACE2 protein expression in some head and neck locations where the epithelia analyzed may be derived from tumor samples. It has recently been reported that in some cancers from different tissue types, the gene expression of ACE2 was significantly higher in normal tissues compared to matched tumors [ 49 ]. Further studies will be required to identify potential factors that may contribute to this change.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that ACE2 expression is stimulated by interferon alpha (IFN-α) in vitro and computationally identified evidence for STAT1, STAT3, IRF8, and IRF1 TFBSs in the ACE2 promoter [ 80 ]. Another recent study has identified correlations of expression between ACE2 and other interferon stimulated genes [ 81 ]. Our analysis produced several putative binding sites for interferon-stimulation mediating TF genes, proximal to the TSSs of the intestine-specific (STAT1, IRF8, and IRF9) and lung-specific transcript (IRF8).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin-(1–7) is a direct product of ACE2, and through binding with the Mas receptor has been shown to advance angiogenesis in injured cardiac tissue (myocardial infarction), by increasing expression of VEGF-D and MMP-9 [ 87 ], and in stroke [ 88 ]. Other studies have suggested that ACE2, either by reducing angiotensin II or through activities of the ACE2/angiotensin-(1–7)/MasR axis, may be negatively associated with angiogenesis in various cancers [ 81 , 89 – 91 ]. It also appears to play a role in angiogenesis in uterus during pregnancy [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Separately, TMPRSS2 cleaves and primes the S protein and drives the fusion of viral and cellular membranes 7 . Similar to Niu et al, Bao et al 8 and Wang et al 2 also found that ACE2 and TMPRSS2 did demonstrate higher expression in patients with lung and gastrointestinal cancers compared with those with other malignancies. In addition, TMPRSS2 is regulated by testosterone and its metabolites, and therefore is suppressed by androgen deprivation therapy in patients with prostate cancer.…”
mentioning
confidence: 64%
“…Certain compositions of the gut microbiota were suggested to be either positively or negatively associated with levels of inflammatory cytokines, and were predictive of severe COVID‐19, possibly through the modulation of fecal metabolites and host immunity 11 . In patients with cancer, Bao et al found that expression of ACE2 and TMPRSS2 were associated with an abundance of specific bacterial genres, with Chlamydia being the top microbiota noted to be positively correlated with ACE2 expression in patients with colorectal cancer 8 . Nevertheless, to our knowledge, our understanding of the ways in which gut microbiota may influence the risk of COVID‐19 in patients with cancer is limited.…”
mentioning
confidence: 99%